ARAH PENGAKUAN, PENGUKURAN, DAN PENYAJIAN ASET BIOLOGIS PADA LAPORAN KEUANGAN PT. SAWIT SUMBERMAS SARANA TBK - IDA SUBAIDA (Relawan Jurnal Indonesia, 2019)
Agricultural companies have different asset classifications from other companies. Assets in agricultural companies are classified as biological assets. The purpose of this study is to analyze the direction of recognition, measurement, and disclosure of biological assets at PT. Sawit Sumbermas Sarana Tbk. The data collection methods carried out in this study are content analysis, literature study, and documentation studies. The analytical method used is a qualitative descriptive analysis method. The results of the study were that PT. Sawit Sumbermas Sarana Tbk in 2018 has recognized, measured, and disclosured its biological assets as biological assets valued at fair value under PSAK no 69 concerning Agriculture. There is a decline in the value of biological assets because of changes in fair value of 53.84%.